Implementation of green chemistry approaches in chemistry labs instruction: A systematic literature review - Lestari, Nanda Ayu; Sulistyowati, Dewi; Dellatiani, Yohana; Irawan, Nisrina Zahira Putri; Fadhilah, Anita; Muyassaroh, Anis (Pascasarjana Universitas Negeri Medan, 2024)
In recent years, the urgent need to address environmental problems has driven green chemistry in various disciplines, focusing on designing chemical products and processes that minimize hazardous materials. This research conducted a systematic literature review (SLR) to evaluate the application of green chemistry in higher education chemistry lab practices and its impact on students' conceptual understanding, practical skills, and environmental awareness. Using the PRISMA method, 46 articles were analyzed from the Scopus and ScienceDirect databases extracted from a total of 537 published between 2015 and 2024. The findings show that applying green chemistry in chemistry laboratory learning can improve students' conceptual understanding, practical skills, and environmental awareness while encouraging environmentally friendly synthesis methods. However, challenges such as limited resources and the need for additional training for lecturers still exist. Institutional support and professional development are needed to maximize implementation. In conclusion, green chemistry has great potential to create a more environmentally responsible generation of chemists, with recommendations for comprehensive integration into chemistry curricula and increased support for educators to address implementation challenges. This study provides a basis for expanding the application of green chemistry in chemistry education and preparing students to face future sustainability challenges.